Analysis of BDS-Impacted Financial Performance: A Testing Direction for New Social Movement Theory - Richatul Jannah; Fitrarena Widhi Rizkyana; Meilani Intan Pertiwi; Tiara Dwi Lestari; Akhila Fuji Safitri; Meldica Widya Ningrum (Akuisisi : Jurnal Akuntansi, 2025)
This study aims to analyze the impact of the BDS Movement on corporate financial performance using the New Social Movement Theory (NSMT) theoretical framework. By combining financial and theoretical aspects, this study is expected to contribute to an understanding of the complex relationship between business, social movements, and corporate financial performance. The BDS movement significantly impacted the performance of these four companies, both in terms of public perception, investor confidence, declining sales, and increased operational pressure. Companies with strong market diversification and risk management strategies, such as PT Fast Food Indonesia, Tbk and PT Unilever Indonesia, Tbk, were able to better weather the impact of the boycott, although they still experienced a decline in profits. On the other hand, PT MAP Boga Adiperkasa Tbk and PT Sarimelati Kencana Tbk showed greater vulnerability to the boycott due to their dependence on a more limited market segment. To survive in such a situation, a more flexible and proactive adaptation strategy is needed in the face of external pressures such as the boycott movement and unstable global economic conditions.